Translating Tempests and Tremblements: Natural Disasters, News, and the Nation in Early Modern England and France - Barker, Sara (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2020)
Early modern people lived at the mercy of their surroundings. In an uncertain world, floods, storms, fires, and earthquakes could affect all levels of society across Europe. But destruction can also lead to creation. Accounts of such disasters were printed as pamphlets and then translated, suggesting a shared experience of disaster that could cross confessional divides. However, a closer look shows that more complex ideas about nation and experience were a feature of these understudied publications. This article focuses on three cases in particular: the storm and lightning strike of 1561, which caused the roof and steeple of St. Paul’s to catch fire; the 1580 English Channel earthquake, which wreaked devastation in both southern England and northern France; and the 1618 fire, which destroyed much of the Palais de Justice in Paris. It investigates how and why accounts of these particular disasters were made and translated. It also questions the role of the nation in how stories were (or were not) transmitted across linguistic, cultural, and national boundaries.